2017
DOI: 10.1002/app.45772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanocrystalline cellulose addition on needleless alternating current electrospinning and properties of nanofibrous polyacrylonitrile meshes

Abstract: Needleless alternating current (AC)-electrospinning is capable of achieving high nanofiber generation rates while adding more flexibility to the process development when compared to common direct current (DC)-electrospinning. However, ACelectrospinning process may produce very different results than DC-electrospinning when using the same precursors. This study demonstrated that stable AC-electrospinning of uniform and mechanically strong polyacrylonitrile (PAN) nanofibrous meshes can be achieved at 30 6 5 kV r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Furthermore, bands due to aliphatic C−H stretching at about 2900 cm −1 (empty circle) and due to C− O stretching (diamond), typical of carbohydrates, were visible in the region ranging from 1200 to 1100 cm −1 . 53 The PDLLA FT-IR spectrum showed the aliphatic C−H stretching bands (filled circle) at 2995 and 2945 cm −1 , the ester CO stretching (empty square) at 1760 cm −1 , and the C−H 3 bending (filled square) at 1454 cm −1 . 62 The FT-IR spectra of electrospun scaffolds are shown in Figure 2 as dark cyan, magenta, and dark yellow curves.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bands due to aliphatic C−H stretching at about 2900 cm −1 (empty circle) and due to C− O stretching (diamond), typical of carbohydrates, were visible in the region ranging from 1200 to 1100 cm −1 . 53 The PDLLA FT-IR spectrum showed the aliphatic C−H stretching bands (filled circle) at 2995 and 2945 cm −1 , the ester CO stretching (empty square) at 1760 cm −1 , and the C−H 3 bending (filled square) at 1454 cm −1 . 62 The FT-IR spectra of electrospun scaffolds are shown in Figure 2 as dark cyan, magenta, and dark yellow curves.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…50 Herein, an El-derived peptide with a bioactive sequence was added to the polymer mixture. CNCs are generally used to reinforce scaffolds electrospun from different polymers, such aspolyvinylidenefluoride-co-hexafluoropropylene (PVDF-HFP), 51 PCL, 52 polyacrylonitrile (PAN), 53 and PLA. 54 In the present study, CNCs were added to counterbalance the strong hydrophobicity of PDLLA and improve the mechanical properties of hybrid scaffolds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An AFES apparatus capable of operating at alternating current (AC)-voltages up to 40 kV rms at 60 Hz was used to spin the precursor bers. [41][42][43]45 The Ti(OBu) 4 /polymer precursor solution was delivered at up to 180 mL h À1 ow rate through the base of a shallow dish-like electrode with the diameter varying from 10 to 25 mm ( Fig. 1).…”
Section: Fabrication Of Tio 2 Nanobersmentioning
confidence: 99%
“…Our previous work has shown that AC electrospinning combined with an appropriately-shaped, needleless spinning-electrode is highly efficient at generating a dense plume of nanofibers at voltages above 30 kV 20 . Subsequent work has shown that the AC collectorless and needleless electrospinning method has the potential for many applications in biomedicine, textile industry, filtration, environmental sensors and enhanced catalists 2124 . We have now created a high throughput method for producing composite yarns with a massive nanofibrous envelope.…”
Section: Introductionmentioning
confidence: 99%